(untitled) (Annual Transactions of the Nordic Rheology Society, 2024)
Graphical abstract: Rheological understanding of blood is relevant for the design of cardiovascular medical devices and implants. Erythrocytes are represented by hydrogel beads dispersed in a continuous glycerol phase. The model system is characterized by aims of optical and rheological characterization. The erythrocyte schematic has been taken from 1. The deformable nature of the hydrogel particles can be seen from the pictures taken during the squeezing experiment (see Fig. 4).